Anticoagulant Control Results among Patients with Mechanical Heart Valves at Muhimbili National hospital, Tanzania (Tanzania Medical Journal, 2008)
Background: Patients with mechanical heart valves receive life long, oral anticoagulant therapy to prevent thromboembolic complications, but this treatment is associated with an increased risk of bleeding (1). However no study in Tanzania has been done to review the adequacy of anticoagulation monitoring and risk factors involved in the operated patients receiving warfarin. Broad objective: The study aimed at reviewing the adequacy of anticoagulant control results among patients with mechanical heart valves attending the anticoagulation clinic at Muhimbili National Hospital (MNH).Study design: This was a retrospective cohort study. Study settings. The study was conducted in Dar es Salaam at the anticoagulation clinic, MNH. Measure of outcome: Review of adequacy of anticoagulation control results was analyzed as percentages of all prothrombin ratio tests done during the whole period of follow up to determine the proportion of tests which were within the therapeutic level, below or above it. Basing on defined percentile levels, the number of patients who were adequately controlled was calculated. Univariate and Multivariate logistic regression was also done to assess factors such as warfarin dose, source, food habits and drugs that could be associated with the high level of anticoagulation Subjects: The study involved all patients-receiving- warfarin with mechanical heart valves operated from 1990 to 2003 attending the anticoagulation clinic at MNH. Methods: Assessment of anticoagulation adequacy was based on the prothrombin ratio measurements that were recorded in the anticoagulation booklets. Each prothrombin ratio measurement was assessed if it was within the therapeutic level, above or below it. Information on risk factors influencing the anticoagulation monitoring was obtained from medical records and interviews. Findings: During study follow-up, a total of 10583 prothrombin ratio measurements were done among all 189 patients who were available for interview. Only 35.5% of the measurements were within the recommended therapeutic (normal) range, 33.4% above therapeutic and 31.1% below it. Thus, in only 35.5% of the follow-up prothrombin ratios, was adequate anticoagulation maintained. The study also only 23.8% (45/189 patients) of the patients were able to maintain adequate anticoagulation for more than 56.5% (more than 80 percentile) of their Prothrombin ratio measurements done during follow up. The occurrence of both thromboembolic and bleeding complications was only significantly reduced when the level of anticoagulation adequacy was above 80 percentile. Conclusions and recommendations: Most of the Prothrombin Time results were out of therapeutic ranges reflecting high anticoagulation inadequacy. It was recommended to improve the anticoagulant adequacy among study patients. Tanzania Medical Journal Vol. 23 (1) 2008: pp. 12-15